Poverty Reduction and Growth Trust : 2016 Borrowing Agreements with Danmarks Nationalbank, the Norwegian Ministry of Finance Representing the Kingdom of Norway, and the Sveriges Riksbank. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
The Fund, as Trustee of the Poverty Reduction and Growth Trust (PRGT or Trust),entered into an amendment of the 2010 borrowing agreement with Danmarks Nationalbank, and new borrowing agreements with the Norwegian Ministry of Finance representing the Kingdom of Norway and the Sveriges Riksbank (hereafter Denmark, Norway, and Sweden, respectively), by which the counterparties will provide new resources to the Loan Accounts of the PRGT in the total amount of SDR 1.1 billion (see attachments). The augmentation under the amendment and the two new agreements are the first three loan contributions to be concluded in the context of the current Board-endorsed effort to raise SDR 11 billion in new PRGT loan resources. These amendment and new agreements became effective on November 17, 2016.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet